Relationship quality in the vertical collaboration of vegetable farmers: evidence from the North China Plain - Gao, Yidan; Zong, Yixiang; Qian, Chen; Bai, Li; Ni, Junwei (Frontiers in Sustainable Food Systems, 2025)
Close collaboration between vegetable farmers and downstream stakeholders is crucial for integrating farmers into modern agricultural supply chains, helping them manage market uncertainties and improving their economic outcomes. Based on the Stimulus - Organism - Response (SOR) model and social embeddedness theory, this study adopts a moderated mediation model and utilizes survey data from 1,014 farmers in the North China Plain to analyze how relationship quality influences vegetable farmers’ participation in the vertical collaboration. Our findings indicate that relationship quality significantly enhances farmers’ willingness to engage in the vertical collaboration, particularly in production contract arrangements. Furthermore, relationship quality promotes collaboration through enhancing farmers’ perceived value, with the business environment significantly moderating this effect. Heterogeneity analyses reveal notable differences, particularly among Chinese cabbage growers and members of agricultural cooperatives, highlighting targeted opportunities for strengthening vertical collaboration. This study emphasizes the need for building robust interpersonal networks among farmers, creating a favorable business environment, optimizing collaboration mechanisms, and implementing targeted policies for different vegetable categories, thereby providing both theoretical insights and practical guidance for agricultural modernization.